Isolation of Functionally Intact Rhodoplasts from Griffithsia monilis (Ceramiaceae, Rhodophyta) - Lilley, Ross McC. (1981)
A procedure is described for isolating photosynthetically active rhodoplasts (“red algal chloroplasts”) from the marine alga Griffithsia monilis. The rhodoplasts exhibited rates of CO(2) fixation and CO(2)-dependent O(2) evolution in the order of 200 micromoles per milligram chlorophyll a per hour when illuminated with red or green light and were approximately 80% intact. The response of the rate of photosynthesis to the inorganic phosphate and pyrophosphate concentrations in the medium was qualitatively similar to that previously reported for spinach chloroplasts. Osmotically shocked rhodoplasts evolved O(2) from ferricyanide in red, but not in green, light and were completely uncoupled. Rhodoplast envelope rupture appeared to be accompanied by phycobilisome loss from the thylakoids.